Infrared measurements of increased CF2Cl2 (CFC-12) absorption above the South Pole - Rinsland, Curtis P.; Levine, Joel S.; Goldman, Aaron; Murcray, Frank J.; Murcray, Frank H.; Murcray, David G. (1988)
An increase in the CF2Cl2 total vertical column above the South pole of 1.24 + or - 0.15 over a 6-year period from 1980 to 1986, corresponding to an average increase of 3.6 + or - 2.1 percent, is found by high-resolution, ground-based solar spectra analyzed in the nu(8) band Q branches at 1161/cm of CF2Cl. This rate of increase is lower than indicated by in situ measurements at the South Pole over the same period, but substantial agreement results when the rather large error margins of the spectral analysis results are considered.